Factors contributing to high failure rate of mat 183 based on students' point of view: A case study in UiTM Pahang branch Raub campus / Nor Hidayah Hassim and Syazwani Zainal Abidin - Hassim, Nor Hidayah; Zainal Abidin, Syazwani (Universiti Teknologi MARA Cawangan Pahang, 2020)
This study was done to identify the factors contributing to the failure rate of MAT183 subject based on the students' point of view. The method used in this study is qualitative research. This study focuses on Computer Science students who failed at least once in this subject to discuss this matter. The data was obtained by gathering a focus group and conduct an open-ended survey. Based on the discussion and interpretation of data, the findings of this study showed that the factors that contribute to the failure rate are the educational background of the students, fear of Mathematics, and lack of exercise or homework in MAT183. To overcome this problem, students need to change their way of studying or learning skills because the main problem lies in their understanding of the fundamentals or basics of Mathematics. The factors that emerged can be controlled by the students themselves. In addition, lecturers' involvement in creating a very positive vibe during teaching can also help to boost interest in MAT 183.